(3ebOeI TQM GdaUhd GdfUjQjI ddCejQ YHO GdhgGH Hf Ydj GdGSJQGHGOjs - (3GdGSJQGHGPj, GdGSJQGHGPj, YHO GdhgGH Hf Ydj GdMSjfj GdGSJQGHGPj, cGf MjG (B875(3g` (B1470(3es ((3CMeO Hf MHjH Rhjf GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3hbHd GdTQhY aj GdebUhO fPcQ ebOeI fGaYI, afbhd(B: (3Ef GdCMcGe GdTQYjI efgG eG jJYdb HcjajI GdYed hjSei aQYjI hYedjI hefgG eG jJYdb HGdGYJbGO hjSei GUdjI hGYJbGOjIs
(3BNQgG (B:s
(3BNQgG(B: (3hdhdG GTJeGdg Ydi GdSeYjGJ cGdCeGeI hGdCeQ HGdeYQha hHYV eHGMK GdeYGfj deG JejR Yf GdadSaI hgPG gh cdGe GdeJCNQjf aJfHg(B.s
(3JHUQI GdYfhGf (B:s
(3PcQ TQM GdaUhd aj GdPQjYI, L (B23: 232s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B2: 343s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs